Systematic Review of the Preclinical Technology Readiness of Orthopedic Gene Therapy and Outlook for Clinical Translation - Wilkinson, Piers; Bozo, Ilya Y.; Braxton, Thomas; Just, Peter; Jones, Elena; Deev, Roman V.; Giannoudis, Peter V.; Feichtinger, Georg A. (Frontiers in Bioengineering and Biotechnology, 2021)
Bone defects and improper healing of fractures are an increasing public health burden, and there is an unmet clinical need in their successful repair. Gene therapy has been proposed as a possible approach to improve or augment bone healing with the potential to provide true functional regeneration. While large numbers of studies have been performed in vitro or in vivo in small animal models that support the use of gene therapy for bone repair, these systems do not recapitulate several key features of a critical or complex fracture environment. Larger animal models are therefore a key step on the path to clinical translation of the technology. Herein, the current state of orthopaedic gene therapy research in preclinical large animal models was investigated based on performed large animal studies. A summary and outlook regarding current clinical studies in this sector is provided. It was found that the results found in the current research literature were generally positive but highly methodologically inconsistent, rendering comparison difficult. Additionally, factors vital for translation have not been thoroughly addressed in these model systems, and the risk of bias was high in all reviewed publications. These limitations directly impact clinical translation of gene therapeutic approaches due to lack of comparability, inability to demonstrate non-inferiority or equivalence compared to current clinical standards and lack of safety data. This review therefore aims to provide a current overview of ongoing preclinical and clinical work, potential bottlenecks in preclinical studies and for translation as well as recommendations to overcome these to enable future deployment of this promising technology to the clinical setting.